IMPLEMENTASI STOP MOTION DALAM PENGEMBANGAN MEDIA PEMBELAJARAN TEKNOLOGI DI TK TRISULA PERWARI - Sindi Dzakiyah Afrah; Aulia Syakinah Maulani; Fadhila Dwi Rahman; Miftakhul Izza Azhari; Suci Utami Putri; Heni Puspita Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the process of implementing stop motion animation-based learning media in the development of technology-based learning at Trisula Perwari Kindergarten. The background of this research is driven by the need for early childhood education institutions to adapt to the increasingly rapid development of digital technology. Stop motion was chosen as a learning medium because it has attractive visual characteristics, is close to children's real experiences, and is able to increase children's focus, imagination, and learning absorption. The research uses a qualitative method with a case study design. Data collection techniques include observation, in-depth interviews, and documentation. The results of the study show that teachers at Trisula Perwari Kindergarten have successfully implemented stop motion-based learning starting from planning, implementation, to learning outcome assessment. The teacher gave a very positive response, stating that this media was able to increase children's involvement, facilitate the delivery of material, increase the variety of learning methods, and encourage students to be more enthusiastic during the learning process. This study concludes that stop motion has great potential to be a learning media innovation that is in accordance with the characteristics of early childhood education in the digital era.